Arrhythmia monitoring and outcome after myocardial infarction (BIO|GUARD-MI): a randomized trial - Jøns, Christian; Bloch Thomsen, Poul Erik; Riahi, Sam; Smilde, Tom; Bach, Ulrich; Jacobsen, Peter Karl; Táborský, Miloš; Faluközy, Jozsef; Wiemer, Marcus; Christensen, Per Dahl; Kónyi, Attila; Schelfaut, Dan; et al. (Frontiers in Cardiovascular Medicine, 2024)
Objectives: Cardiac arrhythmias predict poor outcome after myocardial infarction (MI). We studied if arrhythmia monitoring with an insertable cardiac monitor (ICM) can improve treatment and outcome.Design: BIO|GUARD-MI was a randomized, international open-label study with blinded outcome assessment.Setting: Tertiary care facilities monitored the arrhythmias, while the follow-up remained with primary care physicians.Participants: Patients after ST-elevation (STEMI) or non-ST-elevation MI with an ejection fraction >35% and a CHA2DS2-VASc score ≥4 (men) or ≥5 (women).Interventions: Patients were randomly assigned to receive or not receive an ICM in addition to standard post-MI treatment. Device-detected arrhythmias triggered immediate guideline recommended therapy changes via remote monitoring.Main outcome measures: MACE, defined as a composite of cardiovascular death or acute unscheduled hospitalization for cardiovascular causes.Results: 790 patients (mean age 71 years, 72% male, 51% non-STEMI) of planned 1400 pts were enrolled and followed for a median of 31.6 months. At 2 years, 39.4% of the device group and 6.7% of the control group had their therapy adapted for an arrhythmia (hazard ratio [HR]=5.9, P<0.0001). Most frequent arrhythmias were atrial fibrillation, pauses and bradycardia. The use of an ICM did not improve outcome in the entire cohort (HR=0.84, 95%-CI: 0.65-1.10; P=0.21). In secondary analysis, a statistically significant interaction of the type of infarction suggests a benefit in the prespecified non-STEMI subgroup. Risk factor analysis indicates that this may be connected to the higher incidence of MACE in patients with non-STEMI.The burden of asymptomatic but actionable arrhythmias is large in postinfarction patients. However, arrhythmia monitoring with an ICM did not improve outcome in the entire cohort. Post-hoc analysis suggests that it may be beneficial in non-STEMI patients or other high-risk subgroups.